Autologous Hematopoietic Stem Cell Transplant: A Potential Option for Relapsed Pediatric Acute Myeloid Leukemia With Lack of Matched Sibling Donor and Resource Challenge. Issue 2 (March 2022) - Kalra, Kaushal; Arora, Shalabh; Verma, Saurav; Pushpam, Deepam; Bakhshi, Sameer
Abstract : Though allogeneic hematopoietic stem cell transplant (HSCT) is standard for relapsed pediatric acute myeloid leukemia, often it may not be accessible due to donor unavailability and resource limitations. We retrospectively analyzed outcomes of 26 children (mean age: 10.9±4.5 y) who underwent autologous HSCT in complete remission 2. Three-year event-free survival and overall survival were 50.1±10.7% and 63.3±9%, respectively; with 1 treatment-related death and 46% relapse rate. Notwithstanding the retrospective study design and somewhat favorable patient characteristics, the outcomes are comparable with those of other series and our own allogeneic HSCT data. Autologous HSCT is a potential alternative to allogeneic HSCT, especially in countries with poorly maintained donor registries.